Reflections on the 2021 MCN Editorial Fellowship. Issue 1 (January 2023) - Bernstein, Samantha; Frederick, Anitra; Abbu, Stephanie; DiCioccio, Heather Condo; Thomas, Anisa; Dreisbach, Caitlin
Abstract : Nurse scholars who participated in the 2021 MCN Editorial Fellowship share their experiences. We are now beginning our fourth year of the fellowship and have enjoyed describing our roles as editors with early career nurse scholars and learning so much from them.